The implication of Thorium fraction on neutronic parameters of pebble bed reactor - Zuhair, Zuhair; R. Andika Putra Dwijayanto; Suwoto; Topan Setiadipura (Kuwait Journal of Science, 2021)
Thorium abundance in the Earth’s crust is estimated to be three to four times higher than uranium. This is one potential advantages of thorium as a provider of attractive fuel to produce nuclear energy. Less transuranics produced by thorium during the fuel burnup in the reactor may also be an another advantage for reducing the long term burden of high level long-lived waste. The scope of this paper is to study the implication of thorium fraction on neutronic parameters of pebble bed reactor. Chinese HTR-10 was chosen as the reactor model and the (Th, 235U)O2 fuel was used in this study. A series of calculations with various thorium fraction in (Th,235U)O2 fuel were performed using MCNP6 code and ENDF/B-VII library. The calculation results show that the total temperature coefficient of reactivity of thorium-added pebble bed reactors are generally more negative than those of LEU-fuelled one, except for 10% thorium fraction. The kinetic parameters, especially prompt neutron lifetime and neutron generation time of pebble bed reactors are higher which means the addition of thorium in the fuel makes the reactor more easily controlled. However, the burnup calculations show that the introduction of thorium in the same fuel kernel as LEU within pebble bed reactor is unable to lengthen the fuel residence time. Instead, in all considered thorium fraction, fuel residence time is shorter. The reason is simply because fissile load is decreasing as thorium fraction increases, whilst 233U conversion is far from being sufficient to maintain reactor criticality. It can be concluded that in order to ensure thorium has meaningful share in fission event, its fraction must be kept at least 40%. If the initial fissile load can be kept the same as LEU-fuelled pebble bed reactor, a minimum of 40% thorium fraction can potentially lengthen fuel residence time.